Mesoporous Ce-Zr solid solutions supported Ni-based catalysts for low-temperature CO2 methanation by tuning the reaction intermediates. (15th December 2020) - Xu, Leilei; Wen, Xueying; Chen, Mindong; Lv, Chufei; Cui, Yan; Wu, Xianyun; Wu, Cai-e; Yang, Bo; Miao, Zhichao; Hu, Xun
Graphical abstract: Highlights: Mesoporous Ce-Zr solid solution supported Ni based catalysts for CO2 methanation. The molar ratio of Ce/Zr greatly affected the low-temperature catalytic activity. The redox property of the support promoted the low-temperature catalytic activity. The redox property of the support changed the reaction routes by tuning intermediates. Apparent activation energy could be decreased by employing redox catalytic support. Abstract: We facilely fabricated the mesoporous Ce-Zr solid solutions (Ce/Zr molar ratio = 0–100%) with excellent textural properties and employed them as the supports of the Ni-based catalysts for CO2 methanation. These supported catalysts were systematically measured by various techniques, such as X-ray diffraction (XRD), N2 physisorption, transmission electron microscope (TEM), selective area electron diffraction (SAED), X-ray photoelectron spectroscopy (XPS), H2 temperature-programmed reduction (H2 -TPR), CO2 temperature-programmed desorption (CO2 -TPD), etc. In this catalytic system, the influencing factors of the supports on the promotion of the low-temperature catalytic performances toward CO2 methanation were carefully investigated. Besides, temperature-programmed surface reaction (TPSR) and in-situ diffused reflectance infrared Fourier transform spectroscopy (DRIFTS) of the CO2 methanation were also carried out to investigate the reaction mechanism and the possible reaction intermediates. The kinetic study were also conducted to investigate the apparent activation energies of the CO2 methanation over these Ni-based catalysts with different supports. The influencing factors on the stabilization of the metallic Ni active sites were also investigated by conducting the 40 h stability test over the 15Ni/M-Ce80Zr20 and 15Ni/SiO2 catalysts. It was found that the Ni-based catalysts supported on the mesoporous Ce-Zr solid solutions were provided with advanced low-temperature activity owing to the redox property of the support, which could tune the reaction intermediates and decrease the apparent activation energy during the CO2 methanation.